Clinical analysis of compound a-ketoacid tablets acid to improve the nutrition states and calcium phosphorus metabolism in PD patients - CHEN Hong-yu; ZENG Jia-li (Linchuang shenzangbing zazhi)
Objective To investigate the state of nutrition and calcium-phosphorus metabolism in peritoneal dialysis(PD) patients,and the interference of compound crketoacid tablets.Methods A retrospective study was done from January 2014 to March 2015.260 PD patients from Department of Nephrology,Hangzhou Hospital of Traditional Chinese Medicine were divided into observation group and control group.124 cases in observation group were treated with compound crketoacid tablets(12-15 tablets per day) and 136 cases in control group were given the basic treatment All patients were observed in one year by five time points(baseline,3rd month,6th month,9th month,and 12 th month),including the general conditions,Hb,Alb,BUN,Scr,TG,TCH,LDL,Ca,P,PTH,hsCRP,kt/V,NPCR and Ccr.Results The evaluation of PD adequacy in both groups were up to standard.Malnutrition existed in the baseline of both two groups,especially in observation group.After one-year treatment,the serum Alb,Hb,serum calcium,and phosphorus in observation group were increased significantly,Tch,| LDL and hs-CRP were decreased(P<0.05),and other indexes remained stable.The serum phosphorus and parathyroid hormone level were increased significantly(P<0.05) in control group.Conclusions Compound crketoacid tablets could increase Hb and improve nutritional status,decrease Teh and LDL,increase blood calcium concentration suitably to improve the calcium phosphorus metabolism of PD patients